Textsammlung Europäisches Privatrecht : Vertrags- und Schuldrecht, Arbeitsrecht, Gesellschaftsrecht - Grundmann, Stefan, 1958-; Riesenhuber, Karl (De Gruyter, 2012)
This compilation of texts on European private law makes available to both students and practitioners alike a comprehensive paperback edition of good value focused on the core fields of European private law: contract law, employment law, and corporate law. This edition's special advantage is that it is available in one volume.